Polyphasic taxonomic characterization of bacteria isolated from Chilka Lake, Odisha, India - Mansi, Kwatra (My University, 2013)
Cultivable bacterial diversity of brackish water from Chilka Lake, Odisha was explored in the present investigation. The total bacterial cell count of water samples from Chilka Lake ranged from 1.5 X 105 to 4.5 X 105 cells per milliliter and the cultivability of the bacteria was found to be 9.3%. Close to 189 bacteria were isolated and purified on Zobell marine agar and of which, 52 were of importance as they represented different species belonging to 25 genera, based on the sequences of 16S rRNA gene, and showed 95.0 to 98.0% similarity with their nearest phylogenetic neighbours. These isolates were found to survive at pH 7.0 to 12.0, temperature of 4.0 to 45.0°C and 0-10.0% salinity. Majority of the isolates produced enzymes such as gelatinase, caseinase, urease, DNase, catalase, oxidase, lipase etc. which could be beneficial for biotechnology industry. Amongst the selected strains, ten (CL1-16, CL1-17, CL3-4, CL3-9, CL4a-14, CL4b-2, CL4b-8, CL1R-2, CL2R-4 and CL3R-6) were found to be potentially novel species as they showed ≤98.0% similarity with their phylogenetic neighbours. Further, two isolates-CL1-17 and CL3R-6 showed ≤97.0% similarity with their phylogenetic neighbours and confirmed their species status and named them as Streptomyces indica sp. nov. for CL1-17 and Rheinheimera chilikensis sp. nov. for CL3R-6.
Master of Science-Biotechnology
Keywords: Microbial Diversity; 16S rDNA; Chilka lake; Phylogenetic analysis